(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study examines the buying behaviour of rural consumers towards electric vehicles (EVs) in Gorakhpur, India. A mixed-methods approach was used, combining a survey (n=200) and in-depth interviews (n=20). The findings reveal that while rural consumers are increasingly aware of EVs, adoption is hindered by inadequate charging infrastructure, high upfront costs, and limited product knowledge. However, environmental concerns, government incentives, and lower operating costs drive interest in EVs. The study identifies key demographic and psychographic factors influencing EV adoption, providing insights for policymakers, manufacturers, and marketers to effectively target rural consumers. This research contributes to understanding rural consumer behaviour towards EVs in India, informing strategies to accelerate EV adoption and achieve sustainable transportation goals.